Analysis Of Factors That Influence Employees To Survive - Bangapadang, Stephanie; Sari, Rini Kurnia; Wisnu, Andreas Yoan (Agregat: Jurnal Ekonomi dan Bisnis, 2019)
This study aims to determine the factors that influence employees to survive in a company. The company that we research is PT XYZ. PT XYZ is a company engaged in the digital marketplace industry with marketing areas throughout Indonesia. We assume that employees who survive in a company are due to high employee satisfaction. So that employee satisfaction is always consistent, at least the company always pays attention to the work environment of employees. Compensation, work conflict and work stress are factors that we suspect have an influence on the job satisfaction of PT XYZ employees. This sample was tested on 60 respondents from 80 employees with a sampling technique using the simple random sampling method. The results of this study indicate that the variable compensation, work conflict and job stress affect employee job satisfaction to survive.